THE EXCESS OF GOTHIC IN EDGAR ALLAN POE’S SHORT STORIES AND ABDULLAH HARAHAP’S MANUSIA SERIGALA - Rida Aulia Yasmin; Pepen Priyawan; Udayani Permanaludin (Lire Journal (Journal of Linguistics and Literature), 2025)
Gothic literature has been studied through various lens. However, the study about gothic literature through the lens of gothic excess has not explored. Therefore, this article will discuss about gothic excess comparatively. Gothic writing is considered as writing excess. This excess means a negativity or something that is constructed as a negative. In this context, criminal behavior depicted through the characterization is included to excess of gothic. This criminal behavior is appeared in Edgar Allan Poe’s short stories titled “The Tell-Tale Heart” and “The Black Cat” and Abdullah Harahap’s novel titled Manusia Serigala. These works have similarity in the characterization in order depicted the criminal behavior. It is depicted through the action of the characters murdering other character. The background of this action is depicted differently. In Poe’s works, the action is based on how the characters seeing to other character, while in Harahap’s novel, the Indonesian culture of believing in mystic creature and unnatural ability is involved in portraying the gothic excess. In this article, the researchers will focus on how the characterization portraying excess of gothic in “The Tell-Tale Heart”, “The Black Cat”, and Manusia Serigala using gothic excess theory by Fred Botting. The research is qualitative research. The data is collected from a formal document named short stories anthology and a novel by close-reading and will be analyzed comparatively. The result is the characterization depicted in “The Tell-Tale Heart”, “The Black Cat”, and Manusia Serigala is portraying the excess of gothic. The characterization in these works is considered as criminal behavior that is included as gothic excess.